HIGH-INTENSITY OF GADGET USE INCREASES “CAUTIONS” TOWARD PRESCHOOL CHILDREN DEVELOPMENT - Ningrum Paramita Sari; Yulia Silvani; Mega Ulfah; Sandra Dwi Puspita Sari (Journal of Issues in Midwifery, 2022)
Development is an ongoing process and related to functional matters. One of the factors influencing development is the environment. Excessive and uncontrolled use of gadgets can adversely affect children's motor development, social abilities and communication. This study aims to analyze the relationship between the intensity of gadget use to social personal development, fine motor, gross motor and language in preschool age children (3-6 years). The study subjects were 135 children aged 36 to 72 months. Sampling is done by Purposive Sampling technique. Data retrieval using Denver II Sheet (which has been adapted for use in Indonesia) for early detection examination of child developmental disorders. The results of the study obtained the type of gadgets used by children: 82.5% smartphones, 4.4% tablets, 5.2% smartphones and tablets, 5.2% smartphones and laptops. Based on the type of application used: 8.1% learn (reading, writing, etc.), 35.6% video, 45.9% games and 10.9% puzzles. Meanwhile the intensity of gadget use in preschoolers was obtained 27.4% low intensity, 32.6% medium intensity and 40.0% children using gadgets with high intensity. Chi-square test results showed social personal development p 0.000; fine motor p 0.001; gross motor p 0.069 and language p 0.000.The conclusion of this study is the intensity of gadget use related to the development of social personal, fine motor and language in preschool children (36-72 months).